1983
DOI: 10.1002/zaac.19834990406
|View full text |Cite
|
Sign up to set email alerts
|

Charakterisierung von Distorsionsisomeren der Anionen Pentacyano‐oxo‐molybdat(IV) sowie Tetracyano‐oxo‐aqua‐molybdat(IV) im festen Zustand. Kristallstrukturen von [(C6H5)4P]3[MoO(CN)5] · 7 H2O(grün), [(C6H5)4As]2 [MoO(OH2)(CN)4] · 4 H2O (blau) und [(C6H5)4P]2[MoO(OH2)(CN)4] · 4 H2O (grün)

Abstract: Salze des neuen Pentacyano‐oxo‐molybdän(IV)‐Anions wurden dargestellt: das blaue Cs2H[MoO(CN)5], und blaues [(CH3)4N]2H[MoO(CN)5] · 2 H2O und [Cr(en)3] [MoO(CN)5] · 4 H2O (grün). Das grüne [(C6H5)4P]3[MoO(CN)5] · 7 H2O kristallisiert triklin in der Raumgruppe P1. Das Molybdän(IV) ist von einer terminalen Oxo‐Gruppe (d(MoO): 1,705(4) Å) sowie einer trans‐ständigen CN−‐Gruppe (d(MoC): 2,373(6) Å) und vier äquatorialen CN−‐Gruppen (mittlerer d(MoC): 2,178 Å umgeben. Die blauen und grünen Salze haben unterschie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 11 publications
(2 reference statements)
2
10
0
Order By: Relevance
“…This is also in agreement with monodentate ligand substitution [9][10][11][12][13][14] which also indicated that the aqua molecule is by far the most labile ligand bonded to the metal center which will preferably be replaced as a first step in a bidentate substitution reaction. Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is also in agreement with monodentate ligand substitution [9][10][11][12][13][14] which also indicated that the aqua molecule is by far the most labile ligand bonded to the metal center which will preferably be replaced as a first step in a bidentate substitution reaction. Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The hydroxo complexes are mostly inert towards substitution, whereas aqua complexes are reactive species. The reaction with monodentate ligands (such as, F -, NCS -, N 3 -, CN -and py) gives the aqua substituted complex of the type [MX(CN) 4 (L)] n- [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The protonated oxygen bond length increased from 2.077 (7) 4 ] 2-, respectively [2][3][4]. The same tendency was observed for the corresponding complexes of tungsten(IV), rhenium(V) and technetium(V) [5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 76%
“…It is, however interesting to note that the Re(2)-N(10) bond resulted in a somewhat longer trans-Re Table 3). The ethylenediamine, en, only has a r-donating sp 3 nitrogen donor 4 ] 2-complex that was isolated by Mtshali et al [23] but is significantly shorter than the corresponding bond length of 2.496(7) Å in the same structure that was isolated by Purcell et al [12] (see Table 3). …”
Section: O)(cn) 3 -(L-cn)-ren(cn) 4 ] 4-anion and Five Water Moleculesmentioning
confidence: 86%
See 1 more Smart Citation